2012
DOI: 10.1124/jpet.112.195412
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide-Dependent Kinase-1 and Protein Kinase CδContribute to Endothelin-1 Constriction and Elevated Blood Pressure in Intermittent Hypoxia

Abstract: Obstructive sleep apnea (OSA) is associated with cardiovascular complications including hypertension. Previous findings from our laboratory indicate that exposure to intermittent hypoxia (IH), to mimic sleep apnea, increases blood pressure in rats. IH also increases endothelin-1 (ET-1) constrictor sensitivity in a protein kinase C (PKC) d-dependent manner in mesenteric arteries. Because phosphoinositide-dependent kinase-1 (PDK-1) regulates PKCd activity, we hypothesized that PDK-1 contributes to the augmented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Thus, just like the complex or even conflicting reports on the role of PKC in mediating myocardial protection from ischemia (40), ET-1-PKC interactions are complex. However, recent and growing evidence suggests that PKCd may play the predominant role in ET-1-mediated constriction and blood pressure elevation (41,42). Consistent with these studies, we found that a PKCd-inhibitory peptide significantly attenuated ET-1-induced eNOS mitochondrial redistribution and preserved mitochondrial bioenergetics.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, just like the complex or even conflicting reports on the role of PKC in mediating myocardial protection from ischemia (40), ET-1-PKC interactions are complex. However, recent and growing evidence suggests that PKCd may play the predominant role in ET-1-mediated constriction and blood pressure elevation (41,42). Consistent with these studies, we found that a PKCd-inhibitory peptide significantly attenuated ET-1-induced eNOS mitochondrial redistribution and preserved mitochondrial bioenergetics.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, OSA can impact glycemic control in T2DM, although this relationship was not found in the current cohort (data not shown). Increased advanced glycation end products and alterations in protein kinase C signaling are common pathways by which OSA and hyperglycemia contribute to microvascular complications [ 42 , 43 ]. Through these multiple pathways, OSA could exert adverse effects on diabetes-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…PKC is a multigene large family of serine/threonine kinases which plays important roles in signal transduction in health and disease, contributing to endothelial dysfunction, vascular permeability, angiogenesis, cell growth and apoptosis. Some studies indicated that PKCδ signaling pathway might be involved in ET-1-mediated constriction in mesenteric arteries in IH-exposed rats (Allahdadi et al 2008;Webster et al 2013). Nevertheless, in pulmonary vascular smooth muscle, IH could augment ET-1-induced vasoconstriction through a PKCβ-dependent signaling mechanism (Snow et al 2011).…”
Section: Discussionmentioning
confidence: 99%